Numerical heat transfer study in a round tube with 60 V-shaped rings - Y Kaewkohkiat; S Tamna; W Pairoj; P Promvonge (My University, 2017)
Turbulent flow and heat transfer behaviors in a 3-dimensional isothermal tube mounted repeatedly with 60° V-shaped rings (V-rings) are numerically investigated. The computation based on the finite volume method was conducted for the airflow rate in terms of Reynolds number (Re) in the range of 4000 to 20,000. The ring parameters include three flow blockage ratios, (BR=e/D=0.1, 0.15 and 0.2) and a single ring pitch ratio, PR=1. The computed result shows that friction factor and Nusselt number (Nu) increase with the increment in BR and the maximum thermal enhancement factor (η) of about 1.73 with Nu/Nu0 = 4.5 is found at BR=0.1 and Re=4000. For the need of maximum heat transfer enhancement (Nu/Nu0), the case of BR=0.2 V-ring is selected and modified since this case provides the highest heat transfer. The modification is made by cutting off some area of both ends of the BR=0.2 V-ring and the effect of cutting off (called end-cut ratio, ER=c/e) on thermal performance is also examined. The study reveals that for the end-cut V-ring, the friction factor is considerably decreased while the heat transfer rate reduces moderately with increasing ER. The end-cut V-ring yields the maximum η of 1.64 at ER=0.9, Re= 4000 with Nu/Nu0 = 5.4. Thus, the Nu/Nu0 of the end-cut one is about 20% higher than that of the BR=0.1 V-ring.
Keywords: Isothermal process; Heat transfer enhancement; Friction Factor; Heat Transfer Mechanisms